Effects of Increasing Zn from Zinc Sulfate or Zinc Hydroxychloride on Finishing Pig Growth Performance, Carcass Characteristics, and Economic Return - C. Carpenter; K. Coble; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; S. S. Dritz; J. Usry (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 1,008 pigs [TR4 (Fast × L02 PIC; initially 70.6 lb BW)] were used in a 103-d growth study to determine the effects of Zn source and level on finishing pig growth performance, carcass characteristics, and economic return. The 6 dietary treatments were arranged as a 2 × 3 factorial with main effects of Zn source (ZnSO4; Agrium Advance Technology, Loveland, CO, or Zn hydroxychloride; Intellibond-Z®; Micronutrients, Indianapolis, IN) and level (50, 100, or 150 ppm added Zn). The trace mineral premix was formulated to contain no added Zn. There were 21 pigs per pen and 8 pens per treatment. Overall, there was no effect of Zn source for growth performance criteria observed. Increasing added Zn maximized (quadratic, P = 0.007) ADG when diets contained 100 ppm Zn; however, F/G tended to worsen (source × level, linear, P = 0.068) as Zn from Zn hydroxychloride increased, but was relatively unchanged when pigs were fed increasing Zn from ZnSO4. Carcass yield increased (linear, P = 0.027) as Zn level increased. Pigs fed diets with Zn hydroxychloride had heavier (P = 0.041) HCW, and increased HCW ADG (P = 0.036) than those fed ZnSO4. Hot carcass weight and HCW ADG were maximized (quadratic, P ≤ 0.006) when diets contained 100 ppm Zn. There was a tendency for income over feed cost (IOFC) to be maximized when pigs were fed diets with 100 ppm Zn when economic analysis was calculated on both a constant day (quadratic, P = 0.059) and constant carcass weight (quadratic, P = 0.070) basis, respectively. In summary, these results suggest that a total of 100 ppm added Zn is adequate to maximize ADG, HCW, HCW ADG, and IOFC, but F/G worsened as Zn level increased. Zinc source did not affect growth performance; however, pigs fed Zn hydroxychloride had increased HCW and HCW ADG compared to those fed ZnSO4.
Keywords: finishing pig; zinc hydroxychloride; zinc sulfate